There from the Beginning: The Women of Los Alamos National Laboratory Supporting National and International Nuclear Security - Olga Martin; Laura McClellan; Octavio Ramos; Heather Quinn (International Journal of Nuclear Security, 2022)
From the beginning of the Manhattan Project in the early 1940s, the women of what would become Los Alamos National Laboratory (LANL) worked in technical positions alongside their male counterparts, played a key role as computers, and worked in administrative jobs as secretaries, phone operators, bookkeepers, and on behalf of the U.S. Army in the Women’s Army Corps. Throughout the history of the Laboratory, women experts at LANL helped establish and lead important national and international security programs, with careers in science, technology, engineering, and mathematics. Over time, the women of Los Alamos have come together under various Employee Resource Groups, such as the Atomic Women, to help the next generation succeed in their technical fields. The Laboratory’s commitment to diversity and inclusion continues to this day, with current Laboratory Director Thom Mason leading LANL as the first national laboratory to join the Gender Champions in Nuclear Policy.
Keywords: nuclear security; women in science; women in engineering; gender equality; grassroots movement; career development; pipeline